IDENTIFIKASI MEKANISME KOPING PASIEN GAGAL GINJAL KRONIK DI UNIT HEMODIALIASA RSUD PROVINSI NTB - Dian Istiana; Dewi Nur Sukma Purqoti; Syamdarniati; Zuliardi (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2024)
Cases of Chronic Kidney Failure (CRF) every year increase, CRF is a progressive kidney function disorder and requires treatment in the form of kidney transplantation, peritoneal dialysis, hemodialysis and outpatient for a long time. Patients undergoing hemodialysis experience various problems arising from malfunctioning of the kidneys, affective coping mechanisms are needed in undergoing the treatment process. Objective: Identify coping mechanisms for chronic renal failure patients in the hemodialysis unit of NTB Provincial Hospital. Research method: descriptive research using a cross sectional approach. The sample in this study was 69 respondents, data collection method using Jalowiec Coping Scale questionnaire. Results: most respondents used maladaptive coping, which was 37 people (53.6%). Conclusion: still a large percentage of patients in the maladaptive category so that appropriate interventions are needed to improve the coping of individual CRF patients.